Spanish modals of obligaton: different uses of TENER QUE and NECESITAR - Charland, Bailey (Kansas State University, 2014)
Considerable research exists on the various uses of modals of obligation in English, while the number of studies on Spanish modals is limited. The research of Fairclough (2000) looks at the variation and changes of the Spanish modals DEBER 'should' and TENER QUE ‘to have to’ spoken in Houston. Another study was conducted on modals and their variation in San Juan, Puerto Rico by Jose Santos (1994). However, most of the research does not include the verb NECESITAR 'to need'. This study examines and compares the uses of the modal verbs TENER QUE and NECESITAR. First, this paper presents previous research on modality, the changes and usage of modals in English, and the limited research on Spanish modals. Then the researcher examines the results of data collected using Twitter in order to determine for what main verbs TENER QUE and NECESITAR act as modal verbs, the frequency with which the Twitter users in the Spanishspeaking capitals in Central and South America use these verbs, and in what tense do these two modals occur most often. After discussing the results of the data collection, the study includes a brief discussion on the implications for teaching modals of obligation in Spanish to second language learners. This study finds overall that TENER QUE is preferred over NECESITAR. However, some verbs collocate with NECESITAR more than the average suggesting that patterns of collocations play a key role in determining the use of NECESITAR.
Keywords: Spanish; Linguistics; Modals; Obligation; Foreign Language Instruction (0444); Language, Linguistics (0290)